Kinematics and dynamics of the backstroke start technique - Krüger, T.; Hohmann, A.; Kirsten, R.; Wick, D. (Biomechanics and Medicine in Swimming X, 2006)
The investigation is the lack of complex biomechanical analysis of this starting technique based on kinematic, and dynamic data. Nine male backstroke Sprinters performed four back-stroke Starts over a distance of 7.5 m. During the Start the over all Start time, and split into reaction time, wall time, flight time, and glide time was recorded. Dynamic data were measured as 3-dimensional ground reaction forces. The correlation of the resultant take off force and the final over all Start time (7.5 m) turns out to be significant (r=-.83, p<.01; [n=9]). Correlations were found between the times of hands off and take off (r=.71, p<.05; [n=9]) and hands off and hip entry (r=.93, p<.01; [n=9]). The influence of the kinematic and dynamic parameters of the overwater phase (wall and flight activity) of the backstroke Start technique is clearly shown by the analysis.